2016
DOI: 10.1007/s11684-016-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Coronary leukocyte activation in relation to progression of coronary artery disease

Abstract: Leukocyte activation has been linked to atherogenesis, but there is little in vivo evidence for its role in the progression of atherosclerosis. We evaluated the predictive value for progression of coronary artery disease (CAD) of leukocyte activation markers in the coronary circulation. Monocyte and neutrophil CD11b, neutrophil CD66b expression and intracellular neutrophil myeloperoxidase (MPO) in the coronary arteries were determined by flow cytometry in patients undergoing coronary angiography. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
4
0
2
Order By: Relevance
“…2a) between patients with obstructive coronary artery disease and individuals with normal coronary arteries were observed. These results are consistent with previous studies that demonstrated neutrophil activation may be a unique characteristic for coronary artery ectasia [20]. These results and our ROC analysis suggest that a lower MPXI (< 1.7) is an independent predictor for CAE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2a) between patients with obstructive coronary artery disease and individuals with normal coronary arteries were observed. These results are consistent with previous studies that demonstrated neutrophil activation may be a unique characteristic for coronary artery ectasia [20]. These results and our ROC analysis suggest that a lower MPXI (< 1.7) is an independent predictor for CAE.…”
Section: Discussionsupporting
confidence: 93%
“…Fourth, this study lacked preclinical data to support the selectins-IL-1β-neutrophil activation-NETs axis. Finally, there may be more accurate markers for neutrophil activation and NET formation, i.e., neutrophil CD11b and CD66b are direct markers for neutrophil activation, however, measurement of these markers requires rapid isolation of neutrophils [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage, monocytes were activated by micro-environment of blood and cytokines released by endothelial cells, subsequently transmigrating to the subendothelial tissue and swallowing lipid to differentiate to foam cells [22] . Studies found that leukocytic activation which included neutrophils, monocytes and lymphocytes was connected with the severity of CAD [23] . T cell is an important part of early 'fatty-streak' lesion, accelerating the chronic inflammatory response in progress of lesion formation [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Встановлені зміни відображають загальну реакцію організму обстежуваних і вказують на формування окислювального стресу за участі як ліпідних, так і білкових компонентів, та пригнічення механізмів антиоксидантного захисту, спрямованих на зниження рівня активних форм кисню та продуктів вільнорадикального окиснення макромолекул. Багатьма експериментальними та клінічними дослідженнями доведено, що вільнорадикальна модифікація ліпопротеїнів низької та дуже низької густини на тлі запальної реакції та оксидативного стресу лежить в основі зростання атерогенного потенціалу крові, механізмів ініціації і прогресування атерогенного ураження різних судинних басейнів в організмі [26,27,28]. Тому постало питання визначення активності запальної реакції в організмі студентів у передекзаменаційний період, зокрема наявності запалення низької градації.…”
Section: Kuchmeb@yahoocomunclassified